Fissures in the image of thought: Difference, photography and the networked image. (1st December 2015) - Srbic, Dario
Copy of a copy of a copy of a copy of a copy of … Trent Reznor's formula sounds so much more exciting and seductive than two millennia-old formula of representation and identity also known as A=A. Oversubscribed to central perspective, concerned with clarity and distinctness too content with the content of the image and strongly bonded with its apparatus, photography of the past century repeatedly failed to see the invisible, still acting as a copy of some ideal original, assuming this role from painting. If the painting managed to free itself from representation, what can photography do? With new technologies of image production and dissemination, the pillars of the image of thought begin to crack, with identity and recognition losing the centre stage to difference and repetition. Through the emergence of the ability to photograph everywhere, automated camera and ubiquitous digital dissemination of images, photography is suddenly revealed as the medium of a copy, of uncountable recurrences of the same, and with all of its subjects and objects becoming simulacra, rendering only difference as real and originary.